2006
DOI: 10.1152/ajpregu.00570.2005
|View full text |Cite
|
Sign up to set email alerts
|

Glucose metabolism during lactation in a fasting animal, the northern elephant seal

Abstract: Fasting is associated with a series of physiological responses that protect body tissues from degradation by efficiently using expendable energy reserves while sparing protein. Lactation requires the mobilization of maternal nutrients for milk synthesis. The rare life history trait of fasting simultaneous with lactation results in the conflicting demands of provisioning offspring while meeting maternal metabolic costs and preserving maternal tissues for her own survival and future reproduction. Certain tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
54
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 88 publications
(88 reference statements)
7
54
0
Order By: Relevance
“…This pattern was also observed in the adult males of this study, although the β-HBA concentration was less than 50% that observed in weanling seals, independent of time fasting. Prior reports of mean β-HBA in lactating females indicate an increase from 264 μM early in lactation to 345 μM at the end of lactation (Champagne et al, 2006), which is similar to the values and trend reported for fasting males in this study. In comparison to both elephant seal studies, ketone levels in fasting penguins were 15 times as high at the end of stage 2 fasting (Cherel and LeMaho, 1988).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This pattern was also observed in the adult males of this study, although the β-HBA concentration was less than 50% that observed in weanling seals, independent of time fasting. Prior reports of mean β-HBA in lactating females indicate an increase from 264 μM early in lactation to 345 μM at the end of lactation (Champagne et al, 2006), which is similar to the values and trend reported for fasting males in this study. In comparison to both elephant seal studies, ketone levels in fasting penguins were 15 times as high at the end of stage 2 fasting (Cherel and LeMaho, 1988).…”
Section: Discussionsupporting
confidence: 90%
“…Plasma NEFA, an index of rates of lipolysis, were stable across the fast in males. In contrast, GH, cortisol and NEFA levels increase across the fast in lactating females (Champagne et al, 2006;Houser et al, 2007;Crocker, unpublished data). Despite this increase, rates of lipolysis declined dramatically across the fast in females as adipose tissue proportions were reduced (Houser et al, 2007).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The regulation of aldosterone release by the HPA axis may reflect the need to alter kidney perfusion and lung perfusion during diving, inhibiting typical RAS regulation (Atkinson et al, 2015). In contrast to the juveniles in the current study, aldosterone concentrations increased across the breeding fast in adult male elephant seals (Champagne et al, 2006;Ortiz et al, 2006) in association with RAS activation suggesting that this hormone may be under dual regulation by the HPA axis and RAS.…”
Section: Discussionmentioning
confidence: 53%
“…By extension, substantive glycerol gluconeogenesis should contribute to minimizing the need for other gluconeogenic substrates (e.g., protein) to meet the substrate requirements of all glucose-dependent tissues (e.g., red blood cells). Circulating glucose levels in lactating and recently molted female elephant seals are high, ranging from ϳ6.7 to 7.8 mmol/l, and levels of endogenous glucose production (EGP) are similar to or higher than those observed in non-fasting-adapted species enduring fasts of similar duration (15). The contribution of glycerol to EGP has not been quantified in any fasting seal, and the effect that glycerol gluconeogenesis may have on protein sparing during simultaneous fasting and lactation/molting is unknown.…”
mentioning
confidence: 99%